MAKNA SIMBOLIK TARI GENDONG DALAM PROSESI PERNIKAHAN MASYARAKAT SUKU AKIT DUSUN SEJAHTERA DESA KEMBUNG BARU KECAMATAN BANTAN KABUPATEN BENGKALIS PROVINSI RIAU - Lestari, Fiki Indah; Rosaliza, Mita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The objectives of this study were: (1) to find out the origin of the gendong dance (2) to describe how the process of carrying a gendong dance on the Akit tribal community wedding procession (3) to find out the symbolic meaning of gendong dance (4) to find out the folklore function in gendong for its supporting community (5) to find out the existence of gendong dance in the community. This research was conducted in Dusun Sejahtera, Kembung Baru Village, Bantan sub-district, Bengkalis District, Riau Province. The informants are the elders of the Akit community who are considered to know and master the dance in depth. This method of this research is qualitative by using Roland Barthes's semiotic theory and Levi-Strauss structuralism.The results of this study indicate that gendong dance is part of half-oral folklore which is unknown creator and his inheritance is carried out from mouth to mouth by their generation. In the representation of the symbolic message of the dance consisting of offerings, the attributes used and the dancer's body movements contained a message that was closely related to the myths in the supporting community. This dance as a whole has a meaning as a summon of spirits that are believed to be able to dispose of reinforcements. In the wedding procession, this dance is believed to be able to throw away the reinforcements and give blessings to the lives of the two brides. In dance, there is a symbol that shows how the community interacts with these symbols and the meaning contained in them. The folklore function in gendong dance is a ritual function, a social function, and a tradition preservation function. In the ritual function, namely as a marriage ceremony and treatment ceremony, in a social function that is entertainment for the Akit people while the function of preserving the tradition is as an encouragement for the Akit community in preserving their culture and traditions. Keywords: Gendong Dance, Symbolic Meaning, Function